Roots of Collaboration: Nature-inspired solutions for collaborative networks - Camarinha-Matos, Luis M. (2019)
This work was supported in part by the ARCON-ACM Project and in part by the FCT-Strategic Program under Grant UID/EEA/00066/2013.